Synthesis of 1,4-Disubstituted Pyrazolo[3,4-d]pyrimidines from 4,6-Dichloropyrimidine-5-carboxaldehyde: Insights into Selectivity and Reactivity - Morrill, Christie; Babu, Suresh; Almstead, Neil G.; Moon, Young-Choon (Synthesis, 2013)
Strategies for carrying out the reaction of 4,6-dichloropyrimidine-5-carboxaldehyde with both aromatic and aliphatic hydrazines to generate 1-substituted 4-chloropyrazolo[3,4-d]pyrimidines in a selective, high-yielding, and operationally simple manner are presented. For aromatic hydrazines, the reaction is performed at a high temperature in the absence of an external base. For aliphatic hydrazines, the reaction proceeds at room temperature in the presence of an external base. The observed selectivity and reactivity trends are rationalized through consideration of the proposed reaction mechanism. The 1-substituted 4-chloropyrazolo[3,4-d]pyrimidine products serve as versatile synthetic intermediates, through further functionalization of the 4-chloride moiety, enabling the rapid generation of a structurally diverse array of 1,4-disubstituted pyrazolo[3,4-d]pyrimidines.
Keywords: condensation; hydrazines; hydrazones; nucleophilic aromatic substitution; pyrazolo[3,4-d]pyrimidines